2007
DOI: 10.1016/j.alcohol.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased anxiety and other similarities in temperament of alcoholics with and without antisocial personality disorder across three diverse populations

Abstract: According to Cloninger's model, Type I alcoholics are thought to be innately vulnerable to anxiety and depression. In contrast, Type-II alcoholics are thought to have increased likelihood of antisocial personality disorder (ASPD) and reduced anxiety. However, allostatic activations of stress, anxiety and dysphoria may be a common thread in alcohol use disorders (AUD). Our aim was to find commonalities and differences in temperament of alcoholics with and without ASPD in three diverse populations. By sib-sib co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
3
38
0
3
Order By: Relevance
“…This study showed that although there was no haplotype association with alcoholism per se, alcoholics with high trait anxiety (TPQ harm avoidance) had the highest frequency of the more abundant haplotype, alcoholics with low anxiety had the highest frequency of the less abundant haplotype and non-alcoholics had intermediate frequencies (Enoch et al, 2006). Alcoholics, including those with antisocial personality disorder, have been shown to have higher trait anxiety than non-alcoholics (Ducci et al, 2007;Goodwin and Hamilton, 2003). If trait anxiety does indeed play a role in mediating linkage of GABRA2 haplotypes with alcoholism then the Enoch et al (2006) study would predict that COGA alcoholics have higher trait anxiety than the treatment seeking alcoholics of other studies (Covault et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005).…”
Section: Gaba a Receptor Chromosome 4 Gene Clustermentioning
confidence: 70%
See 1 more Smart Citation
“…This study showed that although there was no haplotype association with alcoholism per se, alcoholics with high trait anxiety (TPQ harm avoidance) had the highest frequency of the more abundant haplotype, alcoholics with low anxiety had the highest frequency of the less abundant haplotype and non-alcoholics had intermediate frequencies (Enoch et al, 2006). Alcoholics, including those with antisocial personality disorder, have been shown to have higher trait anxiety than non-alcoholics (Ducci et al, 2007;Goodwin and Hamilton, 2003). If trait anxiety does indeed play a role in mediating linkage of GABRA2 haplotypes with alcoholism then the Enoch et al (2006) study would predict that COGA alcoholics have higher trait anxiety than the treatment seeking alcoholics of other studies (Covault et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005).…”
Section: Gaba a Receptor Chromosome 4 Gene Clustermentioning
confidence: 70%
“…If trait anxiety does indeed play a role in mediating linkage of GABRA2 haplotypes with alcoholism then the Enoch et al (2006) study would predict that COGA alcoholics have higher trait anxiety than the treatment seeking alcoholics of other studies (Covault et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005). Indeed, it has been demonstrated that COGA alcoholics have higher trait anxiety than non-alcoholics (Ducci et al, 2007). Moreover, supportive evidence comes from the fact that in the Covault et al (2004) study the effect got stronger when alcoholics with major depression (who are likely to have high trait anxiety) were removed.…”
Section: Gaba a Receptor Chromosome 4 Gene Clustermentioning
confidence: 98%
“…43,44 The tension-reduction Figure 4 Levels of a-synuclein mRNA in the hippocampus and hypothalamus of Spontaneously Hypertensive (SHR) and Lewis (LEW) rats (n = 7-8 per strain). Bars represent means±s.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the temperament scales are potential endophenotypes for these behaviors and disorders (Verweij et al 2010). It has been shown that personality traits are considered to be important factors that contribute to the development of AD while AD and personality traits may share genetic components (Cloninger et al 1988;Khan et al 2005;Grucza et al 2006;Ducci et al 2007). Some genes/loci such as DRD4, DYZ3, GAL, 5-HTT, and MAOA, have been suggested to influence both AD and personality traits (Kittles et al 1999;Wiesbeck et al 2004;Belfer et al 2006;Contini et al 2006;Laucht et al 2007).…”
Section: Introductionmentioning
confidence: 97%